Knowledge of Maintaining Dental and Oral Health in Pregnant Women After Using Motion Video Education (MVE) (at Klecorejo Community Health Center, Madiun Regency in 2023) - PAMUDIYA DEWI AZIZA (Poltekkes Kemenkes Surabaya, 2025)
Gingivitis is when the gums become red, swollen, and bleeding. During pregnancy, the hormones esterogen and progesterone increase 10 times higher, so that acid production in the mouth will increase and worsen the condition of the oral cavity. Maintenance of oral health is useful for maintaining the condition of the fetus so that it continues to grow and develop healthily, maintaining good masticatory function so that nutritional needs are met and preventing further oral and dental disease. Problem Statement in this study is the high percentage of pregnant women who experience gingivitis with a percentage of 70% at the Klecorejo Health Center, Madiun Regency in 2023. The purpose of the study was to determine the knowledge of oral health maintenance in pregnant women after using Motion Video Education (MVE) at Puskesmas Klecorejo Madiun Regency. Research method used was descriptive. The research targets were pregnant women who visited the health center, totaling 30 people. Data collection using a questionnaire with data acquisition analysis techniques will be presented in tabular form which is then percentageed and categorized. The results showed that the knowledge of dental and oral health maintenance of pregnant women after using Motion Video Education (MVE) was in the good category.